The Role of The Head of The Islamic Boarding School In Preventing Problems With Teachers of Fiqh Subjects - layyinatul azifah layyinatul azifa; Ainun Nadlif (At-Tarbiyat, 2023)
This research examines the role of the head of Islamic religious schools in preventing problems among teachers of fiqh subjects. Islamic Religious Education subjects are one of the important components in learning fiqh, and teachers' problems in madrasas vary depending on various factors, including the problem category. The research used qualitative descriptive methods and madrasa heads. The research aims to find out and understand teachers' problems in learning fiqh. This research also explored the perceptions of madrasa heads, fiqh subject teachers, curriculum wakakulum, and guidance and counseling teachers. The research uses a qualitative descriptive approach. The research subject involved the head of the madrasah. Data collection was carried out through interviews with madrasa heads, fiqh subject teachers, curriculum wakakulum teachers, guidance and counseling teachers. The data analysis process usually involves several stages, including data reduction, data presentation, and drawing conclusions. The results of this research are that the teacher's problems in learning fiqh at the madrasah have been resolved before the teacher's problems and are in accordance with the rules of educational regulations. Teacher problems in fiqh learning carried out by fiqh subject teachers are in the form of delivering material and learning methods. The conclusion of this research is that the way to solve teachers' problems in learning fiqh is to provide special guidance so that they can be resolved by the head of the madrasah.